Penetapan Harga Pokok Produksi Dalammenentukan Harga Jual dengan Menggunakan Metode Variable Costing (Studi pada Usaha Pabrik Roti Ainayah Kota Ambon) - Dian Sukma Nukuhehe; Kevin Hermanto Tupamahu; Theodora Florence Tomasoa (Universitas Pattimura, 2025)
The determination of the cost of goods manufactured (COGM) is crucial in setting a competitive selling price and ensuring business sustainability. Ainayah Bread Factory in Ambon has faced challenges in accurately calculating COGM due to its reliance on simple methods. This study aims to analyze the application of the variable costing method in calculating COGM and determining the selling price. A descriptive qualitative approach was applied using interviews, observations, and documentation. The findings reveal that the total monthly production cost is Rp205,540,280 with a production capacity of 180,000 breads, resulting in a unit cost of Rp1,141.89. With a selling price of Rp1,300 per unit, the profit margin reached Rp158.11 or 13.84% of revenue. These results confirm that variable costing provides more accurate cost information and supports sound pricing decisions. The condition highlights the enterprise’s potential for growth, efficiency improvement, and long-term competitiveness. The study implies the importance of cost accounting education for SMEs and recommends training on basic financial reporting to strengthen business sustainability.